Virtual reality hypnosis prior to radiofrequency thermocoagulation for patients with chronic pain: an exploratory clinical trial - Safy, Othmane; Rousseaux, Floriane; Faymonville, Marie-Elisabeth; Libbrecht, Dominique; Fontaine, Robert; Raaf, Melissa; Staquet, Cécile; Tasset, Hadrien; Bonhomme, Vincent; Vanhaudenhuyse, Audrey; Bicego, Aminata (Frontiers in Psychology, 2024)
The management of chronic pain may involve an array of tools, including radiofrequency thermocoagulation (Rf-Tc) of sensory nerve terminals. Like many other invasive procedures, Rf-Tc can generate anxiety in a lot of patients, either during the expectation of the procedure or in the course of it. Virtual reality hypnosis (VRH) is a promising tool for managing anxiety and pain in several situations, but its anxiolytic property effectiveness has not been investigated in participantstients with chronic pain and going through a Rf-Tc procedure.Objectives: The goal of this study was to evaluate the effectiveness of VRH for reducing selfassessed anxiety in participantstients with chronic pain, when received in preparation to Rf-Tc.This prospective, quasi-randomized controlled trial was conducted in the Interdisciplinary Algology Centre of the University Hospital of Liège (Belgium).Particiapntstients were randomly assigned to two groups: VRH or Control (usual care).Assessment was carried-out at 4 time points: T0 (one week before Rf-Tc); T1 (pre-intervention, on the day of Rf-Tc); T2 (immediately after the intervention outside of the Rf-Tc room); and T3 (right 30 minutes after Rf-Tc). Medical and socio-demographic data, anxiety trait and state, pain intensity, immersive tendencies, and satisfaction were assessed at each time points, with the primary endpoint being the measurement of anxiety levels.Results: Forty-two participantstients were quasi-randomly assigned to the VRH or Control group. No statistically significant interaction group by time was observed regarding all measured variables, including primary endpoint. However, a significant effect of time was found for anxiety and pain when considering both groups together, towards a progressive reduction.In the context of our study, there appears to be no significant effect of VRH at reducing anxiety in participantstients with chronic pain undergoing Rf-Tc. Anxiety decreases along the procedure, while pain is attenuated by the local anesthetic infiltration of the Rf site.Our results suggest that the presence of a caregiver throughout the procedure might explain the progressive decrease in anxiety. Future randomized controlled trials are needed to precisely study the efficiency of the VRH tool, and the possibility of using it as a complementary treatment for anxiety during invasive procedures.